Digital Shift: How increased Digital Exposure is Reshaping Adolescents Lifestyle? - Monika, Monika; Dube, Shubha (Indian Journal of Extension Education, 2025)
The study was conducted in 2025 to investigate the amount of time adolescents spent on digital devices and its impact on their lifestyle on 300 participants, ranging from 14 to 16 years of age, possessing digital devices in their homes or owned one by them. The findings revealed significant differences between boys and girls regarding activities performed after school. The adolescents were not utilizing digital devices for academic purposes after school hours. The duration of these activities increased during holidays. Adolescents made daily adjustments in their lives to allocate more time to digital devices and conversations with friends. The frequency of use on working days and changes in the duration of these activities during weekends showed significant differences among adolescents. Findings revealed that the participants encountered various lifestyle changes such as anti- social behavior, stress, laziness, tiredness, limited physical interaction, and digital relationships due to prolonged engagement with digital devices. The results of the study demonstrated a positive relationship between lifestyle changes and excessive time spent on digital devices. The findings can assist teachers, educational institutions, policymakers, and counsellors in promoting healthy screen time.
Keywords: Screen time; Digital gadgets; Lifestyle and Adolescents